The Student - as - Customer Metaphor: A Deconstruction Using Foucauldian Constructs - C. Linda Laing; Gregory K. Laing (Australasian Accounting, Business and Finance Journal, 2016)
This paper examines the social impact of the 'student-as-customer' metaphor on the role of academic leadership and objectivity of the assessment process in the higher education sector. A hybrid approach is used in which Deconstruction seeks to render visible the Foucauldian constructs of power and privilege. The paper draws on the existing literature to explore the problematic relationship between the student as customer metaphor, academic leadership, and student assessment. The paper raises awareness of the inherent tensions with the present reliance on the student as customer metaphor and the resulting negative impact on both students and academic staff. This addresses a gap in the literature in regards to the effect that the use of the student-as- customer metaphor has on academic leadership and assessment in higher education.
Keywords: Student-as-customer; Academic leadership; Student assessment; Metaphor; Deconstruction; Foucauldian constructs.